Abu Dhabi International Petroleum Exhibition and Conference 2008
DOI: 10.2118/117109-ms
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Drill Bit Wear Prediction by Combining Rock Energy and Drilling Strength Concepts

Abstract: A central element to reduce drilling cost is to improve drilling operation by analyzing real-time data. Developing advanced real-time analysis tools is one way to improve the drilling operation. Two approaches which currently are used for optimizing the actual rotary drilling process are mechanical specific energy and inverted rate of penetration models. The mechanical specific energy method is defined as the work needed to destroy a given volume of the rock. It can act as a tool during the drilling operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…This will be done using a combination of the ROP models and rock Mechanical Specific Energy. By assuming no bit wear initially and calculating the CCS using the ROP models, it can then be used in conjunction with MSE to calculate the fractional bit wear while drilling (2) as shown below: This approach will give us a new method and tool for predicting real -time bit wear which will help optimize drilling operation in real-time while drilling. It can also be integrated as a module in drilling optimization software after it has been developed, verified and tested.…”
Section: Integrating Rock Mechanical Energy (Mse) and Inverted Confinmentioning
confidence: 99%
See 1 more Smart Citation
“…This will be done using a combination of the ROP models and rock Mechanical Specific Energy. By assuming no bit wear initially and calculating the CCS using the ROP models, it can then be used in conjunction with MSE to calculate the fractional bit wear while drilling (2) as shown below: This approach will give us a new method and tool for predicting real -time bit wear which will help optimize drilling operation in real-time while drilling. It can also be integrated as a module in drilling optimization software after it has been developed, verified and tested.…”
Section: Integrating Rock Mechanical Energy (Mse) and Inverted Confinmentioning
confidence: 99%
“…Bit wear is one of the main causes that affect drilling performance. This work aims to employ more comprehensive ROP models combined with the MSE model through a developed methodology to predict bit wear especially in real time while drilling (2) . A previous methodology was established based on using Burgoyne and Young ROP model for both rollercone and PDC bits which shows uncertainties for the calculated results.…”
Section: Introductionmentioning
confidence: 99%
“…The system uses a newly developed real-time bit wear model (Rashidi et al, 2008) which is a combination method of the rock energy (Mechanical Specific Energy, MSE) model and formation drillbility from the rate of penetration (ROP) model. The ROP and MSE models are competitively using in oil industry to analyze drilling performance and perform a continuous drill-off test respectively.…”
Section: Bit Wear Estimation Modulementioning
confidence: 99%
“…The formation drillability, f 1 is obtained from equation 2. The new real-time bit wear model proposed by (Rashidi et al, 2008), is developed based on equations (1) and (2) and the fractional bit wear can be estimated from the following equations when the bit is in hole:…”
Section: Bit Wear Estimation Modulementioning
confidence: 99%
“…Rashidi et al (2008) have shown that uniaxial compression tests are influenced by several factors, such as the size and shape of the test sample, rate of loading, amount and type of fluid present in the rock sample, mineralogy, grain size, grain shape, grain sorting, and rate of loading. In addition to weathering, rock structure alteration due to diffusion of incompatible fluids and inaccurate handling of the cores in conjunction with stress unloading causes differences between measured rock strength from reality (Nabaei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%